Tahap Patriotisme Golongan Muda di Malaysia: Satu Tinjauan Literatur - Siti Hafizah Yusop; Norbahiah Misran; Noorfazila Kamal; Syaidatun Nazirah Abu Zahrin; Norsaleha Mohd Salleh; Wan Nor Adibah Wan Ahmad; Sarifah Nurhanum Syed Sahur (Universiti Sains Islam Malaysia, 2024)
Sains Insani, Volume 9 Issue 1 Page (93-102)